Effects of Undergoing Multiplex Genetic Susceptibility Testing on Parent Attitudes towards Testing Their Children. Issue 3 (12th December 2013) - Madeo, Anne C.; Tercyak, Kenneth P.; Tarini, Beth A.; McBride, Colleen M.
Abstract: Background: Parents may pursue common disease risk information about themselves via multiplex genetic susceptibility testing (MGST) for their children. Purpose: To prospectively assess whether parents who received MGST disclosed their test results to their child, intended to change the child's health habits, or have the child tested. Methods: Eighty parents who opted for free MGST completed an online survey about a child in their household before undergoing MGST and a follow-up telephone survey 3 months after receiving results. Results: Few parents (21 %) disclosed results to the child. Undergoing MGST was unrelated to intentions to change the child's health habits but did increase parental willingness to test the child. Greater willingness to test a child was associated with positive attitudes toward pediatric genetic testing and intentions to change the child's health habits. Conclusion: The experience of receiving MGST had little impact on parents' perceptions or behaviors related to their minor child.